Assaying the contribution of membrane tension to clathrin-mediated endocytosis - Boulant, Steeve (Clathrin-mediated endoytosis, 2018)
Nowadays, live fluorescent microscopes allow us to study the dynamics of cellular processes in living cells with high spatial and temporal resolution. Since the implementation of this methodology to the field of clathrin-mediated endocytosis (CME), this approach has revolutionized our molecular understanding of clathrin-driven cellular uptake. Conventional live cell microscopy approaches are used to determine the precise functions of specific proteins or lipids in orchestrating CME. Here, we will describe, in depth, the procedure to investigate the contribution of membrane tension in regulating clathrin-dependent endocytosis. We will explain two alternative methods to manipulate membrane tension while performing live fluorescence microscopy: cellular swelling through osmotic shock and cellular stretching of cells grown on stretchable silicon inserts.
Gesehen am 04.07.2019